Studi Pendahuluan Fear Of COVID-19: Bagaimana Orang Memandang COVID-19 - Widhyastuti, Cahyaning (Jurnal Ilmiah Psikologi (JIPSI), 2021)
This study is a preliminary study conducted by researches on how people deal with the COVID-19 pandemic. In this study, researcher wanted to show how people's views of COVID-19. In addition, researcher in this initial study also wanted to see how the validity and reliability of the fear of Covid-19 scale which was the result of language translation. The 71 respondents (21 males) were involved in this preliminary study with the age range of respondents ranging from 17-32 years (M = 21.79, SD = 3,468). The respondents in this study came from several cities in Indonesia with various activity backgrounds. Furthermore, the descriptive analysis in this study was carried out with the help of SPSS for windows version 22. The results of the analysis show that most of the respondents in this study have a moderate level of fear of Covid-19 with a percentage of 73% of respondents. against COVID-19, which is 14% of respondents. Meanwhile, at a low and very high level of fear, there were 13% and 14% of respondents, respectively.